Análisis de la vulneración de los Derechos Humanos generado por el abandono de los adultos mayores en la ciudad de Ibarra - Pineda Flores, Leslie Cecibel (2023)
The present work entitled 'Analysis of the violation of Human Rights generated by the abandonment of the elderly in the city of Ibarra', has as its general objective 'to legally analyze the human rights violated by the abandonment of the elderly in the city of Ibarra during the year 2021, through the documentary review of the pertinent updated sources of information and of the cases denounced in the Board for the Protection of Rights, in the Ombudsman's Office and/or in the Ibarra City Prosecutor's Office, in order to determine if the existing legislation is fulfilling its purpose of safeguarding such rights”. It was developed from a qualitative approach and with a descriptive depth level, being the normative and synthetic analytical methods used, and the research techniques applied, documentary review and analysis, and interviews. The results obtained showed that currently the rights of older adults in the city of Ibarra are being violated in a wide spectrum of aspects such as health, housing, work, food, freedom, autonomy, independence and physical, psychological and sexual integrity, among others. 30 complaints filed before the Cantonal Board for the Protection of Rights were identified during 2021 and 47 during 2022, the competent body having issued protection measures such as family foster care, assistance ticket, fixing alimony, among others. However, the Ombudsman's Office did not follow up on them to verify their compliance, and none of the cases of violation of rights was reported to the Prosecutor's Office, resulting in a situation of impunity, even in the case of older adults in a situation of street. All of this despite Ecuador having a protectionist constitutional and regulatory system that guarantees the rights of this priority attention group.